Penerapan Ecoprint Pada Busana Pesta Fantasi Application Of Ecoprint To Fantasy Party Fashion - Romdhona Chusna Tsani; Laily jaelina Sofiyatur Rohmah (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2024)
. Ecoprint is a type of stamping coloring technique that produces color characteristics in the form of motifs, ecoprint can be applied to fantasy party clothing. The application of ecoprint to fantasy party clothing produces works that are simple but seem luxurious. This fantasy party fashion is a realization of the author's imagination about party clothes that utilize ecoprint techniques. This fabric dyeing technique, has quite a strong appeal among its fans. Fantasy party clothing carries ecoprint techniques in the hope of creating fashion products that are certainly environmentally friendly and reflect the natural wealth of the Blora area, namely teak leaves. This study was designed with the aim of knowing the process of applying ecoprint to fantasy party clothing. The methods used are qualitative methods such as observation, literature, documentation and descriptive data analysis. The steps in the application of ecoprint in fantasy party fashion are making designs, analyzing designs, preparing tools and materials, sizes, archetypes, breaking patterns, cutting materials, merader, sewing, applying ecoprint and finished results. Fantasy party fashion making withecoprint uses bridal satin and organza fabrics. Ecoprint making uses a mordanting technique in which the fabric is steamed for 2 hours. In the process of making ecoprints, you should use shooting glue on the tips of the leaves. This is so that the appearance looks sturdy when used to make variations. Teak leaves used are also prioritized young, so that the color released is maximum and produces the perfect shape in making ecoprints.